Duolingo: Play, Not Pay, to Learn Languages - GOH, Kenneth (Institutional Knowledge at Singapore Management University, 2021)
In July 2021, Duolingo became one of the few mission-driven education-technology companies to list on the Nasdaq Stock Exchange in the US. Founded in 2011 by Luis von Ahn, a Carnegie Mellon professor from Guatemala, and his doctoral student, Severin Hacker, the start-up was born with a social mission to make language learning universally available. A large part of Duolingo’s value proposition was underpinned by free access to all content, game-like lessons, and keeping learners motivated – a recipe that boosted user retention and increasingly, the conversion to paid subscription. Duolingo had enjoyed resounding success, pulling in close to 40 million active monthly users around the globe on its platform. Not only did the firm’s value creation resonate with users (including Bill Gates and Syrian refugees), its exponential growth and positive free cash flow indicating the company’s liquidity – had attracted major investors including Google. In a space where listed firms played to the tune of investors’ quest for more revenue, how could Duolingo balance public markets’ demands for growth and profitability while maintaining its original mission of free education moving forward? Through the story of Luis von Ahn and Duolingo, students will learn how mission-driven firms can integrate social impact with financial goals using technology. In addition, they will be able to apply the BeST Map framework to navigate between the tensions of both goals. They will also understand how a paradox mindset combined with an effectual approach enable innovation in entrepreneurship.